The Questions of War and Peace in Contemporary Islamic Legal Discourse: The Contribution of Wahbah al-Zuḥaylī - Mansoori, Muhammad Tahir (Islamic Studies, 2007)
Wahbah al-Zuḥaylī has come up a legal theory that is, on the whole, consistent with the norms of modern international law and accommodates the realities of the present-day relations obtaining among nations without compromising the objectives of Islamic law as laid down in the Qur’ān and the Sunnah. Al-Zuḥaylī has provided very strong conceptual foundations for a peace-building approach. Anchored in the Qur’ān and the Sunnah, this approach minimizes the use of force, confining it to only extraordinary circumstances. It seeks to promote the values of tolerance, compassion, forgiveness, justice, equity, mutual support and cooperation in intra-human relations. The present article attempts to present Wahbah al-Zuḥaylī’s views on the position of war and peace in Islamic jurisprudence, examines his opinions about issues such as peaceful co-existence, justification of war, norms in the conduct of hostilities, conclusion of treaties between Muslim and non-Muslim states, and other issues relevant to these matters. This article also aims to delineate and highlight the positions taken by Wahbah al-Zuḥaylī which have had an impact on contemporary Islamic thought on these matters.